2018
DOI: 10.3892/etm.2018.5747
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM promotes epithelial to mesenchymal transition and formation of cancer initiating cells in human endometrial cancer

Abstract: Identification of novel factors critical for epithelial to mesenchymal transition (EMT) and cancer initiating cell (CIC) formation may aid in the identification of novel therapeutics for the treatment of endometrial cancer. The present study demonstrated that L1 cell adhesion molecule (CAM) is critical for EMT and formation of CICs in endometrial cancer. Overexpression of L1CAM may promote EMT with increased formation of CICs in HEC-1A endometrial cancer cells. CICs and mesenchymal status resist chemotherapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
2
29
0
1
Order By: Relevance
“…It is intriguing to speculate that Fbxw7 -mutant endometrioid adenocarcinomas (were they left in the body) might have a propensity to progress into UCS, perhaps through the acquisition of Tp53 mutations. This is further suggested by the fact that UCSs are more likely to harbor p53 mutations, and our finding that Fbxw7 -mutant endometrioid adenocarcinomas are more likely to express L1CAM, a marker of EMT (59) frequently overexpressed in UCS (58). However, further investigations will be required to better define the natural history, precursors, and histologic intermediates for UCS.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It is intriguing to speculate that Fbxw7 -mutant endometrioid adenocarcinomas (were they left in the body) might have a propensity to progress into UCS, perhaps through the acquisition of Tp53 mutations. This is further suggested by the fact that UCSs are more likely to harbor p53 mutations, and our finding that Fbxw7 -mutant endometrioid adenocarcinomas are more likely to express L1CAM, a marker of EMT (59) frequently overexpressed in UCS (58). However, further investigations will be required to better define the natural history, precursors, and histologic intermediates for UCS.…”
Section: Discussionmentioning
confidence: 52%
“…We studied 28 cases harboring canonical Fbxw7 mutations (WD40 hotspot or definite null mutations) and 20 cases without Fbxw7 single nucleotide variants leading to amino acid alterations ( SI Appendix , Table S3). All cases were subjected to IHC for L1CAM, a well-established marker for EMT in human ECs (58, 59). Notably, only Fbxw7-mutant tumors expressed L1CAM, and all of these were also p53-positive by IHC, although not all p53-positive cases harbored Fbxw7 mutations ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest that ALK-related cascades could participate in divergent sarcomatous differentiation through the induction of EMT and inhibition of apoptosis [87]. In contrast, although the expression of L1CAM is a strong predictor of poor outcome in endometrial cancer and overexpression of L1CAM has been related to EMT in endometrial cancer cell lines [88], in clinical samples of ECS, only the epithelial component was positive in 65% of the cases, while no expression was seen in the mesenchymal part. Thus in ECS, L1CAM is not a marker for the mesenchymal phenotype [89].…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…In summary, a lot of miRNAs, cellular and circulating, have been found dysregulated in endometrial cancer and a comprehensive list and the relative references are reported in Table 2 [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Ncrnas and Endometrial Cancermentioning
confidence: 99%